Pendampingan penerapan sistem informasi akuntasi pada proses pembuatan kontrak sewa aset PT Kereta Api Indonesia (persero) DAOP 9 Jember - Pratiwi, Ana; Safitri, Dhira Ervina; Artika, Listiana Windi; Zahra, Dewi Lailatul (Penamas: Journal of Community Service, 2023)
Leasing assets of PT Kereta Api Indonesia (Persero) is one of PT Kereta Api Indonesia's (Persero) businesses, apart from passenger and goods transportation services. This business adds to the value of PT Kereta Api Indonesia (Persero)'s income, obtained from tenant asset rental money. The purpose of this study is to describe how the accounting information system is in the process of making asset lease contracts for PT Kereta Api Indonesia (Persero) Operational Area IX Jember. The research method used in this study is a qualitative-descriptive method. PT Kereta Api Indonesia (Persero) has two types of assets: railway and non-railway assets. The results showed that the process of making asset lease contracts for PT Kereta Api Indonesia (Persero) Operational Areas, namely submitting requests for asset leases, surveying rental locations, negotiating processes and making contract books, determining rates, and processing asset lease payments for PT Kereta Api Indonesia (Persero) Regions Operational 9 Jember. As well as following up on the obstacles PT Kereta Api Indonesia (Persero) faced if the debtors did not pay invoices or bills for payment of leased assets of PT Kereta Api Indonesia (Persero) Operational Area 9 Jember.